Mental health of Indigenous Australians: a review of findings from community surveys - Stewart, G; Bourchier, S; Jorm, A; Cvetkovski, S (My University, 2012)
ndigenous Australians have a markedly higher burden of disease and injury than the general Australian population. 1 Most of this has been attributed to higher rates of non-communicable diseases, including mental disorders, but as there are no national data on the prevalence or incidence of diagnosed mental disorders for Indigenous people, proxy measures of relative rates have been used to estimate this component of the burden of disease.
Keywords: Culture -- Indigenous; Health -- Mental; Health and wellbeing; Health; Culture; Indigenous; Mental; Health and wellbeing